2007
DOI: 10.1111/j.1365-2826.2007.01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin‐1 Influences the Excitability of Paraventricular Nucleus Neurones

Abstract: Recent attempts to find novel molecules involved with regulating appetite and energy balance have identified nesfatin-1 as a potent inhibitor of feeding activity (1). This peptide, arising from cleavage of the calcium-binding protein nucleobindin2, is expressed in many hypothalamic nuclei, including the paraventricular (PVN), arcuate, lateral hypothalamic and supraoptic nuclei (1). Significantly, in starved rats, nesfatin-1 levels decreased only in the PVN, a nucleus with a well known association with the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 15 publications
6
47
0
1
Order By: Relevance
“…Similarly to our findings in previous studies we performed in the paraventricular (PVN) and arcuate (ARC) nuclei of the hypothalamus (19,20), nesfatin-1 exerted depolarizing or hyperpolarizing effects on different subsets of mNTS neurons tested. These opposing actions of the same peptide can potentially be attributed to the fact that nesfatin-1 may be affecting functionally separate populations of neurons that ultimately exert differential effects on cardiovascular regulation and energy homeostasis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similarly to our findings in previous studies we performed in the paraventricular (PVN) and arcuate (ARC) nuclei of the hypothalamus (19,20), nesfatin-1 exerted depolarizing or hyperpolarizing effects on different subsets of mNTS neurons tested. These opposing actions of the same peptide can potentially be attributed to the fact that nesfatin-1 may be affecting functionally separate populations of neurons that ultimately exert differential effects on cardiovascular regulation and energy homeostasis.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, central or peripheral injections of nesfatin-1 result in c-Fos expression in NTS neurons (16,22). However, despite the detailed knowledge of the central expression of nesfatin-1, to date there is minimal data describing the specific functional roles of nesfatin-1 in these autonomic nuclei, and what information is available has centered only on actions in the hypothalamus (16,19,20,28,29). The present study was thus undertaken to explore the cellular correlates and functional roles of nesfatin-1 actions in the medullary NTS using current-clamp electrophysiology, post hoc single cell reverse transcriptase polymerase reaction (RT-PCR), and microinjection techniques.…”
mentioning
confidence: 99%
“…A study reported that nesfatin-1 has either hyperpolarizing or depolarizing effects on most neurons in the PVN (39). In addition, glucose and insulin may directly activate nesfatin-1 neurons in PVN (40).…”
Section: Discussionmentioning
confidence: 99%
“…Nesfatin/ NuCB2 expression is modulated by starvation and refeeding in the PVN and SON [3,10]. Nesfatin-1 influences the excitability of a large proportion of different subpopulations of neurons located in the PVN [11]. Nesfatin-1 neurons in the PVN and SON co-expressed oxytocin and vasopressin [10].…”
Section: Peripheral Nesfatin/nucb2 Expressionmentioning
confidence: 99%